siRNA-optimized Modifications for Enhanced In Vivo Activity - Denise M Kenski; Gabor Butora; Aarron T Willingham; Abby J Cooper; Wenlang Fu; Ning Qi; Ferdie Soriano; Ian W Davies; W Michael Flanagan (Elsevier, 2012)
Current modifications used in small interfering RNAs (siRNAs), such as 2'-methoxy (2'-OMe) and 2'-fluoro (2'-F), improve stability, specificity or immunogenic properties but do not improve potency. These modifications were previously designed for use in antisense and not siRNA. We show, for the first time, that the siRNA-optimized novel 2'-O modifications, 2'-O-benzyl, and 2'-O-methyl-4-pyridine (2'-O-CH2Py(4)), are tolerated at multiple positions on the guide strand of siRNA sequences in vivo. 2'-O-benzyl and 2'-O-CH2Py(4) modifications were tested at each position individually along the guide strand in five sequences to determine positions that tolerated the modifications. The positions were combined together and found to increase potency and duration of siRNAs in vivo compared to their unmodified counterparts when delivered using lipid nanoparticles. For 2'-O-benzyl, four incorporations were tolerated with similar activity to the unmodified siRNA in vivo, while for 2'-O-CH2Py(4) six incorporations were tolerated. Increased in vivo activity was observed when the modifications were combined at positions 8 and 15 on the guide strand. Understanding the optimal placement of siRNA-optimized modifications needed for maximal in vivo activity is necessary for development of RNA-based therapeutics.